2003
DOI: 10.1523/jneurosci.23-13-05835.2003
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Patch Electrochemistry: Regulation of Cytosolic Catecholamines in Chromaffin Cells

Abstract: Alterations in the cytosolic pool directly affect neurotransmitter synthesis and release and are suggested to be key factors in various neurodegenerative disorders. Although this cytosolic pool is the most metabolically active, it is miniscule compared with the amount of vesicular transmitter and has never been quantified separately. Here, we introduce intracellular patch electrochemistry (IPE), a technique that for the first time provides direct measurements of cytosolic oxidizable molecules in single mammali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
130
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 128 publications
(148 citation statements)
references
References 61 publications
(72 reference statements)
15
130
1
1
Order By: Relevance
“…In addition, in chromaffin cells, basal concentrations of intracellular catecholamine have been found to be as high as 50 M, and AMPH increases these basal levels 6-fold. The 2 mM DA in the patch pipette to facilitate measurement of DA efflux by the amperometric electrode is in the range of the K m for DA and is in the same order of magnitude as the physiological concentration measured in chromaffin cells (23). We also performed recordings of DA efflux mediated by DAT channel-like activity with 100 M DA in the pipette, and the results were qualitatively similar.…”
Section: Methodsmentioning
confidence: 70%
“…In addition, in chromaffin cells, basal concentrations of intracellular catecholamine have been found to be as high as 50 M, and AMPH increases these basal levels 6-fold. The 2 mM DA in the patch pipette to facilitate measurement of DA efflux by the amperometric electrode is in the range of the K m for DA and is in the same order of magnitude as the physiological concentration measured in chromaffin cells (23). We also performed recordings of DA efflux mediated by DAT channel-like activity with 100 M DA in the pipette, and the results were qualitatively similar.…”
Section: Methodsmentioning
confidence: 70%
“…Background-subtracted cyclic voltammograms served to identify the released substance. The DA oxidation current was converted to concentration on the basis of a calibration of 5 M DA in ACSF after the experiment (Mosharov et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Reduced expression levels of VMAT2 (Mooslehner et al, 2001) or pharmacological inhibition of the transporter (Mosharov et al, 2003) has previously been demonstrated to result in higher dopamine turnover thereby exposing neurons to dopamine-dependent oxidative stress and dopamine-quinone formation. We set up a method to identify dopaminergic neurites, based on the staining of these structures with an antibody against tyrosine hydroxylase (TH) and subtraction of the cell body area using a specialized algorithm (see Materials and Methods).…”
Section: 5mentioning
confidence: 99%